2021
DOI: 10.1111/jspn.12360
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing high‐fidelity simulation to improve newly licensed pediatric intensive care unit nurses' experiences with end‐of‐life care

Abstract: Purpose: New pediatric intensive care unit (PICU) nurses face distinct challenges in transitioning from the protected world of academia to postlicensure clinical practice; one of their greatest challenges is how to support children and their caregivers at the end-of-life (EOL). The purpose of this quality improvement project was to create, implement, and assess the efficacy of a high-fidelity EOL simulation, utilizing the "Debriefing with Good Judgment" debriefing model. Design and methods: Participants were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 23 publications
0
13
0
1
Order By: Relevance
“…Regular SBL sessions were seen to improve nurses' readiness and proficiency (Ballangrud et al, 2014), with the desire for increased duration and frequency of training attributed to the positive learning experience nurses commonly described experiencing during SBL (Ballangrud et al, 2014;Dante et al, 2022;Karlsen et al, 2021;Leclair et al, 2018). This aligns with best practice in nursing education, which recognises that frequent exposure to high-fidelity simulation significantly improves nurses' skill acquisition and maintenance (Anderson et al, 2019;Boling & Hardin-Pierce, 2016;Hardenberg et al, 2019Hardenberg et al, , 2020Hillier et al, 2022;Jung et al, 2023;Karageorge et al, 2020).…”
Section: Discussionmentioning
confidence: 96%
“…Regular SBL sessions were seen to improve nurses' readiness and proficiency (Ballangrud et al, 2014), with the desire for increased duration and frequency of training attributed to the positive learning experience nurses commonly described experiencing during SBL (Ballangrud et al, 2014;Dante et al, 2022;Karlsen et al, 2021;Leclair et al, 2018). This aligns with best practice in nursing education, which recognises that frequent exposure to high-fidelity simulation significantly improves nurses' skill acquisition and maintenance (Anderson et al, 2019;Boling & Hardin-Pierce, 2016;Hardenberg et al, 2019Hardenberg et al, , 2020Hillier et al, 2022;Jung et al, 2023;Karageorge et al, 2020).…”
Section: Discussionmentioning
confidence: 96%
“…In addition, pain also affects the psychological reaction of patients, and patients with gastric cancer have various degrees of anxiety, depression, irritability, and other negative emotions, which not only directly affect the QOL of patients but also have a negative impact on the recovery of the disease. Hillier et al (2022) [30] found that pain control in postoperative gastric cancer patients was affected by a variety of factors, including patients' emotions, analgesic methods, ward environment, and management level of medical staff. At the same time, patients' attitude and cognitive level toward pain and analgesic drugs directly affect patients' ability to control pain and the nal analgesic effect.…”
Section: Discussionmentioning
confidence: 99%
“… 46 Simulation training may better prepare staff with effective communication and clinical skills. 49 Finally, nursing and allied health staff may experience frustration about their limited role and participation in end-of-life decision-making. 23 , 41 , 44 Interdisciplinary team support and institutional practices including joint approaches to symptom control, routine team meetings, ethical competency training, and robust discussions sharing perspectives may overcome these challenges.…”
Section: Discussionmentioning
confidence: 99%
“…In response, international nursing organizations have emphasized importance of robust palliative care instruction in curricula . Simulation training may better prepare staff with effective communication and clinical skills . Finally, nursing and allied health staff may experience frustration about their limited role and participation in end-of-life decision-making .…”
Section: Discussionmentioning
confidence: 99%